"There Was a Time of Dancing"—Visual Memory of the Maya Uprising in Guatemala, 1980–1981. Issue 4 (20th October 2022) - Palencia Frener, Sergio
Abstract : Guatemala's imagery of the war has been mostly construed from the standpoint of state militarism and violence. In the 1980s photos of rebellious Maya villages scarcely appeared in international publications, all of which were forbidden in Guatemala. Using a historical anthropological approach, visual memory, and ethnography of the Maya highlands, this essay delves into the photography of Megan Thomas and Luis Felipe González, two militants of the Guerrilla Army of the Poor who, in 1980 and 1981, took pictures of Mam and Akateko Maya villages during the uprising. Through fieldwork in San Miguel Acatán and Guatemala City, interviews with former indigenous and non-indigenous insurgents, conversations with the photographer Megan Thomas, and archival research in Guatemala and Mexico, this essay proposes to rethink the war in highland Guatemala through visual materials, spoken stories, and indigenous memories.